Numerical Modeling of RC Columns and a Modified Steel Model Proposal for Elements With Plain Bars - Melo, José; Varum, Humberto; Rossetto, Tiziana (Frontiers in Built Environment, 2020)
The cyclic earthquake loads may accelerate the bond degradation and consequently lead to important bar slippage. The bond-slip mechanism is assumed as a common cause of damage or collapse of existing RC structures loaded by seismic leads. The RC structures designed and built before the implementation of the modern seismic codes and with plain reinforcing bars are particularly affected by the bond degradation. However, perfect bond is assumed in most of the numerical models. The numerical modeling results of two RC columns tested under cyclic lateral load are presented in this paper. One column is built with plain reinforcing bars and the other with deformed reinforcing bars and both have structural detailing typically adopted in pre-1970's structures. For each column, different software and modeling strategies to simulate the cyclic response were adopted. The frameworks OpenSees and SeismoStruct were used to develop the numerical models which were calibrated based on the experimental results. A simple modeling strategy was adopted in the OpenSees models to consider the bond-slip effects. A modified tri-linear steel material model is proposed and adopted to contemplate the slippage of plain reinforcing bars by reducing the steel Young modulus. The tri-linear steel model parameters were obtained empirically based on the experimental results.